A Case of X-Linked Hypophosphatemic Rickets with Dentin Dysplasia in Mandibular Third Molars - Rena Okawa; Masakazu Hamada; Misato Takagi; Saaya Matayoshi; Kazuhiko Nakano (MDPI AG, 2022)
X-linked hypophosphatemic rickets (XLH) is a disease characterized by impaired bone mineralization, and its dental features include gingival abscesses and large pulp spaces due to dentin dysplasia. A 20-year-old woman with XLH was referred to oral surgery for extraction of mandibular third molars. She was diagnosed with XLH at approximately 1 year of age and was treated thereafter. There was no history of gingival abscesses, and panoramic radiographic and computed tomographic examinations revealed no evidence of dentin dysplasia. However, histopathological examination of the extracted teeth showed dentin dysplasia, including interglobular dentin. In this XLH patient, dentin dysplasia was revealed histologically even though no obvious abnormality was found on visual and radiographic examinations. These findings suggest that in patients with XLH, oral management must take dentin dysplasia of the permanent teeth into consideration even if the patient's general condition is well controlled with conventional therapy.